Visual and skill effects on soccer passing performance, kinematics, and outcome estimations - Basevitch, Itay; Tenenbaum, Gershon; Land, William M.; Ward, Paul (Frontiers in Psychology, 2015)
The role of visual information and action representations in executing a motor task was examined from a mental representations approach. High-skill (n = 20) and low-skill (n = 20) soccer players performed a passing task to two targets at distances of 9.14m and 18.29m, under three visual conditions: normal, occluded, and distorted vision (i.e., +4.0 corrective lenses, a visual acuity of approximately 6/75) without knowledge of results. Following each pass, participants estimated the relative horizontal distance from the target as the ball crossed the target plane. Kinematic data during each pass were also recorded for the shorter distance. Results revealed that performance on the motor task decreased as a function of visual information and task complexity (i.e., distance from target) regardless of skill level. High-skill players performed significantly better than low-skill players on both the actual passing and estimation tasks, at each target distance and visual condition. In addition, kinematic data indicated that high skill participants were more consistent and had different kinematic movement patterns than low skill participants. Findings contribute to the understanding of the underlying mechanisms required for successful performance in a self-paced, discrete and closed motor task.